RIWAYAT BERAT BADAN LAHIR RENDAH DENGAN KEJADIAN STUNTING PADA ANAK USIA DIBAWAH DUA TAHUN DI KOTAMOBAGU - St. Rahmawati Hamzah; Alhidayah A; Khafia Khairun Nisa Mokodompit; Darmin D (Penerbit Yayasan Daarul Huda Kruengmane, 2022)
Stunting cases in Indonesia are still a serious problem with a prevalence of 24,4%, this figure has not met the WHO recommended target of 20%. Stunting data in North Sulawesi shows a prevalence rate of 21.6% and in Kotamobagu it is 25,1%. One of the factors causing stunting cases is low birth weight (LBW). The aim of the study was to analyze the relationship between low birth weight and the incidence of stunting in children under two years old in Kotamobagu. The type of research used is an analytic observational design with a case control study design with a retrospective approach. The research samples were 44 cases and 44 controls. The sampling technique uses Simple random sampling. Data were collected using a structured instrument and analyzed univariately and multivariately with the Chi-Square test. There is a relationship between low birth weight and the incidence of stunting in children under two years of age (OR=40,600; 95% CI, 8,622-191,178 p=0,000). This means that LBW children have a 40,6 times greater risk of being stunted compared to children born with normal weight. Because the OR value> 1, low birth weight (LBW) is a risk factor for stunting in children under two years old in Kotamobagu City. It is suggested to health workers and stakeholders in Kotamobagu to provide assistance and empower nutrition intake for pregnant women and continue to intensify the movement for the first 1000 days of life.